High throughput microparticle production using microfabricated nozzle array - Celik, Suleyman; Celik, Umit; Kosar, Ali; Kilic, Abdulhalim (Royal Soc Chemistry, 2025)
Polymeric microparticles have triggered critical advancements in drug delivery systems, offering significant improvements in therapeutic efficacy by controlling the delivery while minimizing adverse side effects of the pharmaceuticals. However, conventional microparticle fabrication techniques face several limitations, such as particle size variability, early drug degradation, and production inefficiencies. In this study, we developed a microparticle production system (MPS) in which a precision spraying technology was integrated with a microfabricated nozzle array-based piezoelectric transducer. High-throughput microparticle production was achieved using Poly(d,l-lactide-co-glycolide) (PLGA) dissolved in dichloromethane (DCM) and dimethyl carbonate (DMC). The resulting PLGA microparticles exhibited remarkable consistency in size uniformity with an average diameter of 8.9 +/- 1.7 mu m. Detailed characterization through scanning electron microscopy (SEM) and focused ion beam (FIB) analyses revealed distinct surface and internal structures and demonstrated the effect of solvent volatility on microparticle morphology. Chloramphenicol (CHL) was used as a model drug, and an encapsulation efficiency of 38.7% and a loading efficiency of 16.2% were achieved. The PLGA microparticles showed sustained CHL release and demonstrated effective antibacterial activity against Escherichia coli (E. coli), highlighting their potential for controlled therapeutic applications. This developed MPS system offers a scalable and efficient approach for producing PLGA-based microparticles with controlled drug release profiles, making it valuable in the industrial-scale production of advanced drug delivery technologies.
Keywords: Drug-Delivery Systems; Manufacturing Techniques; Polymeric Nanoparticles; Plga; Release